The genesis of the AIDS policy and AIDS Space in Brazil (1981-1989) - Sandra Garrido de Barros; Ligia Maria Vieira- (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To analyze the genesis of the policy for controlling AIDS in Brazil. METHODS Socio-historical study (1981-1989), based on Bordieu's genetic sociology, by document analysis, bibliographical review, and in-depth interviews. It consisted of a connection between the analysis of the paths of 33 agents involved in the creation of a social space focusing on AIDS-related issues and the historical possibility conditions of the drafting of a specific policy. RESULTS AIDS Space is a gathering point for the paths of agents from several social fields (medical, scientific, political, and bureaucratic fields). A specific space for relationships, which enabled the drafting of a policy for controlling the AIDS epidemic, but also a place where the authority to talk about the meaning of the disease, the methods to prevent and treat it was under dispute. The analysis showed how the various structures (democratic administrations in Sao Paulo and at the national level, with public health officers taking important positions) and the lack of a specific therapy contributed to social agents of different ranks and backgrounds to initially set prevention as a priority. CONCLUSIONS The rise of the sanitary movement, the organization of SUS, and the dominance of the medical field at the AIDS Space contributed to foster treatment as a part of the measures to control the epidemic. These conditions allowed drafting a policy based on the integrality of care, by linking prevention and treatment in the following decade, with important participation from state bureaucracy and researchers.